PENGARUH AKTUALISASI DIRI DAN PENGHARGAAN TERHADAP KINERJA PENYULUH PERTANIAN PADA BADAN PELAKSANA PENYULUHAN PERTANIAN, PERIKANAN DAN KEHUTANAN KABUPATEN MUSI BANYUASIN - Rumbiati Rumbiati (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this research is to the effect of the effect of self-actualization and appreciation of the work performance. This research was conducted at the Badan Pelaksana Penyuluh Pertanian dan Petrikanan Kabupaten Musi Banyuasin. Software used in the study is Eviews 6.0 with the 157 respondents. This study found that of partial self-actualization variable is a negative effect to performance. While of appreciation a positif effect to performance. While a simultaneous the self-actualization dan appreciation effect on performanceKeyword : employee, self-actualization, appreciation, and work performance